Komunikasi Interpersonal antara Guru dan Orang Tua melalui Percakapan Online (Whatsapp) di SDN Cilangkap 03 Depok - safitri, Desya Safitri; Salsabila, Najwa Inaya; Masduki, Muhammad (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2023)
Abstract The purpose of this study was to find out how the teacher's interpersonal communication relationship with the parents of students at SDN Cilangkap 03 in WhatsApp social media. The object of this research is the homeroom teacher and parents of students at SDN Cilangkap 03. The method used in this research is a qualitative method. Data collection was carried out by randomly interviewing homeroom teachers and students’ parents according to the required criteria. The results of the study show that interpersonal communication between teachers and guardians of students in online conversations (WhatsApp) will be successful if the teacher starts approaching students' parents first. To establish effective and healthy interpersonal communication, a teacher must have the mindset that I am a fun person and can make friends with anyone. Keywords: interpersonal communication, parents, WhatsApp, teachers, interpersonal relationships Abstrak Tujuan penelitian ini adalah untuk mengetahui bagaimana hubungan komunikasi interpersonal guru dengan orang tua siswa SDN Cilangkap 03 dalam media sosial WhatsApp. Objek penelitian ini adalah guru wali kelas dan orangtua siswa SDN Cilangkap 03. Metode yang digunakan dalam penelitian ini ialah metode kualitatif. Pengambilan data dilakukan dengan wawancara kepada guru wali kelas dan orang tua siswa secara acak sesuai kriteria yang dibutuhkan. Hasil penelitian menunjukan bahwa komunikasi interpersonal antara guru dan wali murid di dalam percakapan online (WhatsApp) akan berhasil apabila guru memulai pendekatan terlebih dahulu kepada orang tua siswa. Untuk menjalin komunikasi interpersonal yang efektif dan sehat, seorang guru harus memiliki pola pikir bahwa saya adalah orang yang asyik dan dapat berteman dengan siapapun. Kata kunci : komunikasi interpersonal, orangtua siswa, WhatsApp, guru, Hubungan interpersonal